2019
DOI: 10.3389/fneur.2019.00053
|View full text |Cite
|
Sign up to set email alerts
|

The Investigation of the Cardiovascular and Sudomotor Autonomic Nervous System—A Review

Abstract: The autonomic nervous system as operating system of the human organism permeats all organ systems with its pathways permeating that it is involved with virtually all diseases. Anatomically a central part, an afferent part and sympathetic and parasympathetic efferent system can be distinguished. Among the different functional subsystems of the autonomic nervous system, the cardiovascular autonomic nervous system is most frequently examined with easily recordable cardiovascular biosignals as heart rate and blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(117 citation statements)
references
References 84 publications
1
97
0
9
Order By: Relevance
“…Furthermore, age, patient medication, consumption of nicotine, alcoholics or caffeine or even room temperature in the examination room are important influencing factors in autonomic functional diagnostics. Therefore, strict standardization of patient preparation, test procedures and evaluation using standard values and test algorithms created for all laboratories is required [119].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, age, patient medication, consumption of nicotine, alcoholics or caffeine or even room temperature in the examination room are important influencing factors in autonomic functional diagnostics. Therefore, strict standardization of patient preparation, test procedures and evaluation using standard values and test algorithms created for all laboratories is required [119].…”
Section: Discussionmentioning
confidence: 99%
“…The study documents that ESC is associated with the presence of CAN and DPN and is related to the degree of impairment of neurological measures. Previous studies, using the gold‐standard for sudomotor function QSART, have shown weak correlations between sweat volume of lower limb and feet ESC, and recent reviews have described in detail the differences between these techniques assessing sudomotor function . Thus, the use of ESC as a marker of distal autonomic function seems to be supported although a conclusive demonstration of its direct assessment of sudomotor function is lacking.…”
Section: Discussionmentioning
confidence: 99%
“…ESC is based on an electrochemical reaction between sweat chloride and stainless steel electrodes in response to applied low voltage direct current, 35 thus it reflects the flow of chloride ions from sweat glands to the skin caused by an electric current through the activation of the sympathetic sudomotor fibers or a direct stimulation of sweat glands. 15,36…”
Section: Sudomotor Function Assessmentmentioning
confidence: 93%
See 2 more Smart Citations